VD_FINDINFO Pron / 2013 / 230 vom 19. September 2013 - VD Tribunal cantonal (2013)
CONDITION DE RECEVABILITÉ, ASSISTANCE JUDICIAIRE | 117 let. b CPC (CH), 132 CPC (CH), 236 CPC (CH), 308 al. 2 CPC (CH), 319 let. b CPC (CH), 56 CPC (CH)